Penerapan Balanced Scorecard Dalam Penilaian Kinerja Aparatur Pelayanan Publik - Rahayu Mardikaningsih; Ella Amalia Ningsih; Fina, Fina Dwi Amelinda; Wahyu Nashirul Haq; Didit Darmawan (LPPM STISIP IMAM BONJOL, 2026)
The Balanced Scorecard has demonstrated its potential as an effective tool in encouraging the reformulation of public sector performance measurement systems, particularly in service personnel. This study aims to explore the adaptation of the Balanced Scorecard in measuring the performance of state civil servants (ASN) to suit the characteristics and needs of the public sector, and to assess the influence of ASN understanding, human resource capacity, and indicator integration on the quality of performance measurement. The method used is a qualitative literature study, with thematic synthesis of various relevant articles, books, and official documents to obtain a comprehensive picture of the implementation of the Balanced Scorecard in the public service sector. The results show that the Balanced Scorecard, originally developed for the business sector, has been successfully adapted into a performance measurement instrument that emphasizes four perspectives: finance, customers, internal processes, and growth and learning. This adaptation is able to reflect budget effectiveness, public satisfaction, operational process efficiency, and ASN capacity development. The success of the Balanced Scorecard implementation is highly dependent on ASN's strategic understanding of the indicators, the ability to internalize perspectives, and the capacity of human resources to analyze and optimize performance data. Without adequate internalization and integration, performance measurement tends to be formalistic and less reflective of public service effectiveness. This research confirms that the Balanced Scorecard is not simply an administrative evaluation tool, but a strategic instrument that can improve the accountability, service quality, and effectiveness of public organizations.